Digestibility of Betung Bamboo Fiber Following Fungal Pretreatment - Fatriasari, Widya; Syafii, Wasrin; Wistara, Nyoman J.; Syamsu, Khaswar; Prasetya, Bambang (UI Scholars Hub, 2014)
This research evaluated the effect of fungal pretreatment of betung bamboo fibers and enzymatic- and microwaveassisted hydrolysis on the reducing sugar yield. The enzymatic hydrolysis of the pretreated biomass was carried out with cellulase and 10 and 20 FPU/g of substrate in a shaking incubator at 50 °C and 150 rpm for 48 h. The sulfuric acid concentration used in the microwave-assisted acid hydrolysis was 1.0, 2.5, and 5%, either with or without the addition of activated carbon. Microwave irradiation (330 Watt) was applied for 5–12.5 min. The yield of reducing sugar was better with the microwave-assisted acid hydrolysis, and the yield tended to increase with an increase in the irradiation time. Based on the dry weight of the initial biomass (bamboo), pretreatment with 5% inoculum loading resulted in a higher reducing sugar yield (17.06%) than with 10% inoculum loading (14.54%). At a 1% acid concentration, the formation of brown compounds decreased, followed by a reduction in the reducing sugar yield. The addition of activated carbon at a 1% acid concentration seemed to be of no benefit with respect to the yield in the microwaveassisted acid hydrolysis. The pretreatment with the 5% inoculum loading for 12.5 min at 1% acid concentration resulted in the highest reducing sugar yield. Under these conditions, the yield was 6.3-fold that of the reducing sugar yield using 20 FPU/g of cellulase. The rate of bamboo hollocellulose hydrolysis reached 22.75% of the maximum theoretical reducing sugar reducing sugar of dry biomass.